Introduction of a national program for HbA1c testing in Guyana South America and initial results. (December 2019) - Lowe, J.; Singh, K.; Sukhraj, K.; Rambaran, P.; Lebovic, G.; Ostrow, B.
Abstract: Diabetes is an increasing challenge for low- and middle-income countries (LMIC) and access to HbA1c testing is limited. HbA1c, a measure of glycaemic control averaged over 3 months, provides both clinicians and policymakers with a tool to identify the risk of long-term diabetes comorbidity. We describe the steps used to implement standardised testing in Guyana South America and the initial results according to a locally developed protocol as part of a country-wide project to improve the care of people with all forms of diabetes The steps identified include: a standardised method traceable to a recognized international reference standard, participation in a quality control cycle with an international reference laboratory, a clinical pathway for testing to reduce inappropriate use and minimize resource wastage, training of technicians in operation and maintenance of equipment, identification of a suitable space with constant power supply, a reliable procurement system, education of healthcare professionals on interpretation and follow-up of results and feedback of programme results to improve clinical practice. Some steps for implementation of the national HbA1c testing program were initiated better than others. Initial unreliability of the service undermined confidence in the system. Failure to follow the testing protocol led to some patients being tested too soon and others too late. Cost of reagents was about 5.60 USD/test. We trained 340 people in diabetes care and knowledge was improved but were unable to assess whether it was appropriately applied. Over one third of people tested in the 30–70 age group had an HbA1c over 9% (75 mmol/mol) and this did not improve over the 5 years of testing. Despite the difficulties we think our unique experience of implementation of a nationwide HbA1c testing programme has important lessons for other LMICs.